2022
DOI: 10.3390/v14112471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Staphylococcus aureus Strain Background on Sa3int Phage Life Cycle Switches

Abstract: Staphylococcus aureus asymptomatically colonizes the nasal cavity of mammals, but it is also a leading cause of life-threatening infections. Most human nasal isolates carry Sa3 phages, which integrate into the bacterial hlb gene encoding a sphingomyelinase. The virulence factor-encoding genes carried by the Sa3-phages are highly human-specific, and most animal strains are Sa3 negative. Thus, both insertion and excision of the prophage could potentially confer a fitness advantage to S. aureus. Here, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Expression of rRNA is controlled by the concentration of the transcription-initiating nucleotide (iNTP) within the promoter 11 . Analysis of potential transcriptional start sites upstream of qoxABCD predict an ATP as the transcription-initiating nucleotide (based on data from 32 )(Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of rRNA is controlled by the concentration of the transcription-initiating nucleotide (iNTP) within the promoter 11 . Analysis of potential transcriptional start sites upstream of qoxABCD predict an ATP as the transcription-initiating nucleotide (based on data from 32 )(Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that in addition to the interplay between CI, Mor, and RecA, host-specific factors and additional phage regulatory genes are also involved in determining the mobility of φ13 and other S. aureus phages [ 37 ] . This opens new possibilities for discovering important regulatory mechanisms beyond the CI:Mor switch.…”
Section: Discussionmentioning
confidence: 99%
“…AlphaFold2 (AF2) models for individual φ13 proteins were either from the Alphafold database (Q2FWP6 and Q2FWP7, model version 4) [35] or constructed using the Colab version of Alphafold2 [36] using default parameters. TP901-1 CI-NTD was modeled using the full-length TP901-1 CI wild-type sequence with no templates.…”
Section: Modeling With Alphafold2mentioning
confidence: 99%
“…Importantly, NcOs identification may allow to uncover functional relationships between neighbouring genes that would otherwise go unnoticed. After the first description of the NcO architecture in Staphylococcus aureus (Sáenz-Lahoya et al 2019 ), gene arrangements consistent with an NcO structure have been detected in Bacillus subtilis (Johnson et al 2020 ), the phytopathogenic bacterium Dickeya dadantii (Forquet et al 2022 ), a temperate phage of the Siphoviridae family from S. aureus (Rohmer et al 2022 ) and large DNA viruses such as varicella, Epstein–barr, and Baculovirus (Prazsák et al 2018 , Fülöp et al 2022 , Torma et al 2022 ). Altogether, these examples support the idea that NcOs are not exclusive to bacteria and are also present in the genomes of phages and viruses.…”
Section: Introductionmentioning
confidence: 99%